Relationship between solvent retention capacity and protein molecular weight distribution, quality characteristics, and breadmaking functionality of hard red spring wheat flour - Hammed, Ademola Monsur; Ozsisli, Bahri; Ohm, Jae-Bom; Simsek, Senay (AACC International, 2015)
This research aims to investigate the relationship between the solvent retention capacity (SRC) test and quality assessment of hard red spring (HRS) wheat flour samples obtained from 10 HRS cultivars grown at six locations in North Dakota. The SRC values were significantly (P < 0.05) correlated with flour chemical components (protein, gluten, starch, and damaged starch contents, except arabinoxylan); with farinograph parameters (stability [FST], water absorption, peak time [FPT], and quality number); and with breadmaking parameters (baking water absorption [BWA], bread loaf volume [BLV], and symmetry). Differences in locations and cultivars contributed significantly to variation in quality parameters and SRC values. Suitability of SRC parameters for discriminatory analysis of HRS wheat flour is greatly influenced by molecular weight distribution (MWD) of SDS-unextractable proteins. SRC parameters, except for sucrose SRC, showed significant (P < 0.01) and positive correlations with high-molecular-weight (HMW) polymeric proteins in SDS-unextractable fractions, whereas only lactic acid SRC exhibited significant (P < 0.01) correlations with low-molecular-weight polymeric proteins. HMW polymeric proteins also exhibited positive associations with FPT, FST, BWA, and BLV. The discrepant variation in association of SRC parameters with respect to MWD of SDS-unextractable proteins could improve segregation of HRS wheat flour samples for quality.